Effects of Melatonin Supplementation in Type 2 Diabetes Mellitus - Setiawan Nathan, Daniel; Yumilia, Hoo (International Medical Journal Corp. Ltd, 2024)
Background: Diabetes mellitus, a metabolic illness causing hyperglycemia, is primarily caused by insulin resistance. Melatonin, an indolamine, plays a role in the circadian cycle and affects hunger, fullness, and awareness. Melatonin treatment has shown positive effects on glycated hemoglobin, fasting plasma glucose, and insulin levels, but may increase insulin sensitivity and reduce fasting insulin levels. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using PubMed, ScienceDirect, and SagePub, among other online venues. Result: Our study team initially collected more than 100,000 publications using reliable sources including Science Direct, PubMed, and SagePub. Just five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. To facilitate viewing, Table 1 gathers together the literature that was examined for this analysis. Conclusion: Melatonin, a hormone, can affect glycemic control, obesity control, and energy expenditure. It regulates insulin secretion and protects against reactive oxygen species and free radicals. However, high levels can negatively affect insulin sensitivity.